2017
DOI: 10.1007/978-981-10-5203-3_10
|View full text |Cite
|
Sign up to set email alerts
|

Technological Developments in lncRNA Biology

Abstract: It is estimated that more than 90% of the mammalian genome is transcribed as non-coding RNAs. Recent evidences have established that these non-coding transcripts are not junk or just transcriptional noise, but they do serve important biological purpose. One of the rapidly expanding fields of this class of transcripts is the regulatory lncRNAs, which had been a major challenge in terms of their molecular functions and mechanisms of action. The emergence of high-throughput technologies and the development in var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
240
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(253 citation statements)
references
References 188 publications
1
240
0
1
Order By: Relevance
“…LncRNAs are defined as a cluster of transcripts with more than 200 nucleotides without protein‐coding potential, which were originally considered as transcriptional noise. However, more and more evidence suggested that lncRNAs were involved in the regulation a wide range of cellular processes, and more importantly, play different roles in cancer stem‐like properties . For instance, lncRNA LUCAT1 plays an essential role in regulating breast cancer stemness .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs are defined as a cluster of transcripts with more than 200 nucleotides without protein‐coding potential, which were originally considered as transcriptional noise. However, more and more evidence suggested that lncRNAs were involved in the regulation a wide range of cellular processes, and more importantly, play different roles in cancer stem‐like properties . For instance, lncRNA LUCAT1 plays an essential role in regulating breast cancer stemness .…”
Section: Introductionmentioning
confidence: 99%
“…However, more and more evidence suggested that lncRNAs were involved in the regulation a wide range of cellular processes, and more importantly, play different roles in cancer stem-like properties. [18][19][20] For instance, lncRNA LUCAT1 plays an essential role in regulating breast cancer stemness. 21 Another lncRNA NEAT1 has been shown to promote stem-like properties in glioma cells.…”
Section: Introductionmentioning
confidence: 99%
“…2 Limited clinical treatment can slow down tumor growth to improve the life of patients with HCC. [4][5][6] LncRNAs are defined as transcripts with over Yun-Zhi Yin and Wei-Hua Zheng are co-first authors. 3 Recently, growing evidence has indicated the significance of long noncoding RNAs (lncRNAs) in various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is one of the most common cancers worldwide, and colon adenocarcinoma (COAD) is a common type of CRC [1]. Considerable advancements have been made in the study of COAD in recent years, but the mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA, a type of RNA that was once was viewed as transcriptional "noise" without biological functions and protein-coding capacity, is defined as a type of RNA transcript of more than 200 nucleotides [1]. Recently, lncRNAs were reported to be closely involved in CRC.…”
Section: Introductionmentioning
confidence: 99%